Mental health, where are we now?: a sociological analysis of the integration of mental health into primary healthcare in the Kingdom of Eswatini - Dlamini, Zenanile Zoe (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
This is a qualitative study exploring the integration of mental health into primary healthcare in the Kingdom of Eswatini. Primary healthcare forms the basis of any healthcare service provision. Primary Healthcare for mental health is an essential component of any well-functioning health system. Making mental healthcare available in primary healthcare allows for early detection and early treatment while it is still easier and cheaper. Purposive sampling was used to recruit nursesand a government official in the Hhohho region in the Kingdom of Eswatini.The study found that there are major challenges in the primary health care clinics, and this negatively affects the WHO (2001) proposal on mental health integration into primary health care. This finding is similar to other low-income countries' challenges in mental health integration into primary health care. The impact of neo-liberal policies on healthcare in Eswatini is explored and it is clear these policies impact the ability of the Ministry of Health to provide health care. The study also drew on the symbolic interaction perspective to understand the meanings that nurses attach to mental illness and their experiences mental health care.
Keywords: Mental health services -- Eswatini; Psychiatric hospitals -- Eswatini; Primary health care -- Eswatini; Mentally ill -- Services for -- Eswatini; Mental health policy -- Eswatini